Hubungan Antara Beban Kerja Mental Dengan Stress Kerja Mahasiswa Pekerja - Roziana Ainul Hidayati; Alif Sulthon Basyari (Jurnal Manajerial, 2025)
Background – Studying while working is not easy. When demands exceed a person's resources and abilities, their mental health can be affected. Various risks of studying while working can occur, and there is evidence that fatigue and insomnia are common among working students. According to research conducted by Allison Vaughn, a research psychologist from San Diego University, students who also work are at greater risk of experiencing mental health problems. Stress is a mismatch between a person and their environment, resulting in their inability to cope with the various demands placed on them, according to physiological, behavioral, psychological, and somatic symptoms and signs. Based on the results of research by Hidayati (2023), it was found that the average level of Mental Workload of working students at the Faculty of Economics and Business, Muhammadiyah University of Gresik is categorized as high with an average score of 77.64. Aim – This study aims to determine whether there is a relationship between mental workload and work stress among working students at the Faculty of Economics, Muhammadiyah University of Gresik Design / methodology / approach – This study employed a quantitative method with a cross-sectional approach. Accidental sampling was used for sample collection. The measurement tools included the NASA-Task Load Index (TLX) form to measure mental workload and the Job Stress Scales (JSS) questionnaire to assess stress experienced by working students. The Pearson Correlation Test (Pearson Product Moment Correlation) was used to analyze the relationship between mental workload and work stress among working students. Findings – The majority of respondents, 54.41%, reported a very high mental workload. The Mental Workload Indicator that most significantly influenced the mental workload of working students at the Faculty of Economics, Muhammadiyah University of Gresik, was the Temporal Demand (TD) Indicator. The majority of respondents, 69.12% of working students at the Faculty of Economics and Business, Muhammadiyah University of Gresik, reported experiencing moderate work stress. The correlation test revealed no relationship between mental workload and work stress. Research implication – There is a need for time management for working students to reduce the mental workload they experience and it is necessary to identify the causes of work stress in themselves.   Limitations – This research has a research object limitation, namely at the Faculty of Economics and Business, Muhammadiyah University of Gresik, specifically for students who are also workers.